Xylo-Oligosaccharides, Preparation and Application to Human and Animal Health: A Review - Chen, Yuxia; Xie, Yining; Ajuwon, Kolapo M.; Zhong, Ruqing; Li, Tao; Chen, Liang; Zhang, Hongfu; Beckers, Yves; Everaert, Nadia (Frontiers in Nutrition, 2021)
Xylo-oligosaccharides (XOS) are considered as functional oligosaccharides and have great prebiotic potential. XOS are the degraded products of xylan prepared via chemical, physical or enzymatic degradation. They are mainly composed of xylose units linked by β-1, 4 bonds. XOS not only exhibit some specific physicochemical properties such as excellent water solubility and high temperature resistance, but also have a variety of functional biological activities including anti-inflammation, antioxidative, antitumor, antimicrobial properties and so on. Numerous studies have revealed in the recent decades that XOS can be applied to many food and feed products and exert their nutritional benefits. XOS have also been demonstrated to reduce the occurrence of human health-related diseases, improve the growth and resistance to diseases of animals. These effects open a new perspective on XOS potential applications for human consumption and animal production. Herein, this review aims to provide a general overview of preparation methods for XOS, and will also discuss the current application of XOS to human and animal health field.